FUNGSI LEMBAGA PEMASYARAKATAN SEBAGAI TEMPAT UNTUK MELAKSANAKAN PEMBINAAN DAN PELAYANAN TERPIDANA MATI SEBELUM DIEKSEKUSI - Budiyono, Budiyono (Faculty of Law, Universitas Jenderal Soedirman, 2009)
Penitentiary was a place to conduct coaching Educate Prisoners and Child Socialization. There are pro-death penalty views (Retensionist) and cons of death penalty (abolitionist) on the existence of death penalty and execution. This issue is causing problems from the aspect of regulation that is the basis of service provision on death row since capital punishment on all the services there are no specific rules. The problem is the placement and service must be performed by the prisons before the execution on death row, before it is executed on death row man alive who is naturally still have rights that must be protected as a right to physical care and health until the corresponding executable , including also get their rights, as for the rights referred to was referring to the provisions of Article 14 of Act No.12/1995 about Correctional. Kata kunci : Lembaga Pemasyarakatan, Pidana mati, Peraturan khusus